Hеzbollah's Election Victory in Lebanon in 2018 - Vinarov, Ivan (Research Papers, 2020)
The current research aims is to present the essence of the Lebanese electoral system and to analyze the results of the last parliamentary vote, to examine the current political situation in the country. The US Congressional Research Service information ranges, some basic normative and international law documents, and the content–analysis of media information are also used. The main conclusion is that Lebanon needs a government of national unity, but this does not coincide with the interest of many external actors – mainly Iran and Saudi Arabia.
Keywords: Sunnis; Confessional democracy; Christian block; Maronites; Muslim block; Shiites